Concept of the minimum energy passenger car with use of unconventional energy sources - Gabrinets, V. A.; Tytarenko, I. V. (Science and Transport Progress, 2014)
Purpose. The paper is aimed to consider the concept of creation of the minimum energy passenger car with use of nonconventional energy sources and the walls that have enhanced thermal insulation properties. Мethodology. The types of heat losses, as well as their value were analyzed. The alternative sources of energy are considered for heating. Their potential contribution to the overall energy balance of the passenger car is analyzed. Impact on the car design of the enhanced wall thermal insulation, solar energy inflow through the transparent windows and energy release of passengers are quantitatively evaluated. Findings. With the maximum possible use of all unconventional energy sources and the rational scheme solutions of conditioning and heating systems energy the costs for these needs for a passenger car can be reduced by 40-50%. Originality. New types of energy to maintain the heat balance of the car in the winter period is proposed to use firstly. New schematics solutions for environmental control system of the car both in winter and in summer periods were offered. Practical value. Introduction of the proposed scheme solutions and approaches to ensure the comfortable conditions for passengers may be implemented on an existing park of passenger cars and do not require a major re-equipment of systems that have already been installed.